Contract, labour law, and the realities of working life - Schofield-Georgeson, Eugene, 1982- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book offers a critical and timely account of how labour law has become a means for protecting employers rather than workers. The past few decades have witnessed something of a 'silent revolution' in the traditional protective role that labour law has played in the lives of workers. While this transformation has been overt in the realm of the market and at the level of the legislature, the role of the judiciary in this process remains significantly under-studied. Focusing on Australia, but drawing also on material from New Zealand, the UK and Canada, this book investigates how the common law has intervened to shape labour law in the image of commercial contract, determining disputes and defining legal issues by ignoring the realities of working life. Under this new conception of labour law, industrial relations between workers and employers are rarely reciprocal or relational. Rather, they are determined by the legal meaning and purpose of the contract of employment, drafted by lawyers for the benefit of employers and their human resources departments. Having demonstrated how approaches to contractual formalist legal reasoning have redefined labour law, this book goes on to propose an array of innovative legal and policy strategies to restore the protective role of labour law to the employment relationship. Scholarly, but also accessible to students, this book will appeal to those with interests in labour law, contract law and sociolegal studies"--
The employee / contractor distinction & casual employment : preferring the employer's contract over the worker's reality -- Implied terms : reality in historical perspective and the neoliberal approach -- Adverse action : ... at the employer's convenience -- Contract and collective bargaining : neither compulsory, nor voluntary bargaining -- redesigning collective-bargaining in the image of employer power -- The right to strike in the shadow of contract law -- What can be done?
Keywords: Collective bargaining -- Law and legislation; Labor laws and legislation; Labor contract; Industrial relations; LAW / Labor & Employment; BUSINESS & ECONOMICS / Workplace Culture